Analisis Perbedaan Gejala Kemoterapi Siklus 1-6 pada Pasien Kanker Nasofaring Berbasis Pengkajian “Esas” di Murni Teguh Memorial Hospital - Audy Denada, Shara; Banjarnahor, Seriga (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Cancer is one of the leading causes of death worldwide. Nasopharyngeal carcinoma attacks the lymph nodes. The treatment that can be done is chemotherapy. Chemotherapy will cause symptoms, and one tool that can be used in assessing chemotherapy symptoms is ESAS, which is used to assess: pain, fatigue, nausea, depression, anxiety, drowsiness, loss of appetite, decreased well-being, and shortness of breath. Objective: To analyze the differences in chemotherapy symptoms in cycles 1-6 in nasopharyngeal cancer patients based on the ESAS assessment at Murni Teguh Memorial Hospital. Methods: A descriptive quantitative research method was used. The instrument used was a questionnaire. The results showed that moderate pain was experienced by 38.7% of patients, mild fatigue by 41.9%, mild nausea by 41.9%, no depression by 77.4%, anxiety in the no problem category (71%), drowsiness in the no problem category (48.4%), good appetite in the severe category (41.9%), feeling fresh and fit in the no problem category (58.1%), and shortness of breath in the no problem category (64.5%). The implications of this study are: 1. Minimizing or reducing the effects of chemotherapy in each chemotherapy cycle in nasopharyngeal cancer patients. 2. The results of this study can contribute to the development of oncology nursing science